Exploring the formation and electronic structure properties of the g-C3N4 nanoribbon with density functional theory. (19th March 2018) - Wu, Hong-Zhang; Zhong, Qing-Hua; Bandaru, Sateesh; Liu, Jin; Lau, Woon Ming; Li, Li-Li; Wang, Zhenling
Abstract: The optical properties and condensation degree (structure) of polymeric g-C3 N4 depend strongly on the process temperature. For polymeric g-C3 N4, its structure and condensation degree depend on the structure of molecular strand(s). Here, the formation and electronic structure properties of the g-C3 N4 nanoribbon are investigated by studying the polymerization and crystallinity of molecular strand(s) employing first-principle density functional theory. The calculations show that the width of the molecular strand has a significant effect on the electronic structure of polymerized and crystallized g-C3 N4 nanoribbons, a conclusion which would be indirect evidence that the electronic structure depends on the structure of g-C3 N4 . The edge shape also has a distinct effect on the electronic structure of the crystallized g-C3 N4 nanoribbon. Furthermore, the conductive band minimum and valence band maximum of the polymeric g-C3 N4 nanoribbon show a strong localization, which is in good agreement with the quasi-monomer characters. In addition, molecular strands prefer to grow along the planar direction on graphene. These results provide new insight on the properties of the g-C3 N4 nanoribbon and the relationship between the structure and properties of g-C3 N4 .